Asset Pricing with Countercyclical Household Consumption Risk - CONSTANTINIDES, GEORGE M.; GHOSH, ANISHA (Journal of Finance, 2017)
ABSTRACT We show that shocks to household consumption growth are negatively skewed, persistent, countercyclical, and drive asset prices. We construct a parsimonious model where heterogeneous households have recursive preferences. A single state variable drives the conditional cross‐sectional moments of household consumption growth. The estimated model fits well the unconditional cross‐sectional moments of household consumption growth and the moments of the risk‐free rate, equity premium, price‐dividend ratio, and aggregate dividend and consumption growth. The model‐implied risk‐free rate and price‐dividend ratio are procyclical, while the market return has countercyclical mean and variance. Finally, household consumption risk explains the cross section of excess returns.